EKSEKUSI TERHADAP PIDANA TAMBAHAN BERUPA UANG PENGGANTI PADA TINDAK PIDANA KORUPSI OLEH KEJAKSAAN NEGERI PADANG (Studi Putusan Nomor: 19/Pid.Sus-TPK/2015/PN Pdg) - Yusuf, M (UNES Law Review, 2018)
Broadly speaking, the execution is one of the jurisdiction of the prosecutor as regulated by the law to enforce the judge's decision, as well as the additional criminal under Article 10 point (b) of the Criminal Code and Article 18 Paragraph (1) of Law Number 31 Year 1999 regarding Eradication of Corruption. In fact it is undeniable that corruption is currently one of the extraordinary crimes that have an impact on the state's financial losses, which are of the essence in returning the state's losses, particularly with regard to the execution of additional crimes in the form of substitute payments on corruption. The problems in this thesis are: Firstly, how is the execution process of additional criminal in the form of replacement money on corruption crime by Padang State Attorney ?. Secondly, what are the obstacles encountered by the Padang District Attorney in the execution of additional crime in the form of substitute money on corruption and how is the effort to overcome these obstacles?. Specification of this research is an analytical descriptive research. Approach method used is normative juridical as main approach and supported by empirical juridical approach. The data used are secondary data and primary data. The data obtained were analyzed qualitatively and presented analytically descriptively. Based on the research and discussion it can be seen that: First, the process of execution of additional crime in the form of replacement money on corruption crime by State Prosecutor of Padang is done through execution of court decision which has obtained legal force still done by prosecutor, after the clerk sends a copy of decision letter to him, this requires that a new execution be exercised by the prosecutor, after the clerk has sent a copy of the verdict to him, so the defendant refuses to be executed on the basis of the quotation of the permanent verdict in addition to the court's verdict giving no legal basis on the property of the accused that has been confiscated. This is based on the task of the Prosecutor as the executor to execute in accordance with existing legislation. Second, the obstacles encountered by the Padang District Attorney in additional criminal execution in the form of substitute money in corruption are the absence of a standard rule governing the execution mechanism, including guidance if the defendant is unable to pay for all or part of the additional penalty imposed. The easy access to double identity card making it difficult to trace the convicted property, the duration of the judicial process until the verdict has the legal power to keep the execution and the number of convicts who prefer to go through the additional criminal sanction of the additional criminal. While the efforts made by the State Prosecutor Padang is to reform the legislation related to the authority of the Public Prosecutor Office through the Attorney General to seize the assets of someone suspected of having committed a criminal act of corruption that harm the state finances.